Alternating 5,5-Dimethylcyclopentadiene and Diketopyrrolopyrrole Copolymer Prepared at Room Temperature for High Performance Organic Thin-Film Transistors - Fei,Z; Chen,L; Han,Y; Gann,E; Chesman,ASR; McNeill,CR; Anthopoulos,TD; Heeney,M; Pietrangelo,A (Journal of the American Chemical Society, 2017)
We report that the inclusion of nonaromatic 5,5-dimethylcyclopentadiene monomer into a conjugated backbone is an attractive strategy to high performance semiconducting polymers. The use of this monomer enables a room temperature Suzuki copolymerization with a diketopyrrolopyrrole comonomer to afford a highly soluble, high molecular weight material. The resulting low band gap polymer exhibits excellent photo and thermal stability, and despite a large π–π stacking distance of 4.26 Å, it demonstrates excellent performance in thin-film transistor devices.